Desa Sebagai Unit Pemerintahan Terendah Di Kota Pariaman - Hengki Andora (Fakultas Hukum Universitas Riau, 2011)
Pariaman apply two system of lowest government in its region, namely the system of Desa and system of Kelurahan. Number of desa is 55 Desa and number of Kelurahan is 16 Kelurahan. Pariaman not want to apply the system of Nagari, with arguing: i) in rural communities have felt comfortable with the system of Desa (status quo); i) the establishment of Nagari government system will cause a reduction in the allocation of development fund from the goverment; iii) Pariaman already heterogenous society; and iv) the establishment of Nagari system will cause loss public office and employment for people who sit in the Desa institutional structures. Desa in Pariaman performed in accordance with Local Regulation No. 7 of 2007 on Desa. Institutional Desa consist of Desa government, Badan Permusyawaratan Desa (BPD), and another Desa Institutional.